Elucidation of the Sodium – Copper Extrusion Mechanism in CuCrS2: A High Capacity, Long‐Life Anode Material for Sodium‐Ion Batteries. Issue 5 (24th August 2018) - Krengel, Markus; Hansen, Anna‐Lena; Hartmann, Felix; van Dinter, Jonas; Bensch, Wolfgang
Abstract: The compound CuCrS2 with a quasi‐layered crystal structure was investigated as room temperature rechargeable sodium‐ion battery electrode. It exhibits excellent performance as anode material with a high reversible capacity of 424 mAh g −1 at 700 mA g −1 after 200 cycles and a capacity retention of 98.6 % compared to the third cycle. Results of ex‐situ X‐Ray diffraction experiments performed at different stages of the discharge process demonstrate that at the beginning of Na uptake, Cu + cations are reduced to nanosized metallic Cu particles which are expelled from the host lattice. Simultaneously, Na is inserted into the host material leading to the formation of Na0.7 Cu0.15 CrS2 with significantly expanded interlayer space. Metallic Cu and Na0.7 Cu0.15 CrS2 coexist at this stage of discharge. Increasing the amount of Na per formula unit leads to successive conversion to X‐ray amorphous Cr, nanocrystalline Na2 S and metallic Cu. The formation of highly disordered metallic Cr with domain sizes in the range of few nanometres is revealed by atomic pair distribution function analysis. During the charge process, the nanocrystalline Cu particles are retained and Na0.7 Cu0.15 CrS2 is at least partially reformed. The finely distributed Cu particles dramatically improve the long‐time stability as evidenced by comparison of the electrochemical behaviour of mere NaCuCrS2 . Abstract : Get out of my way : The sodium – copper extrusion mechanism of CuCrS2 is studied using ex‐situ XRD measurements, Rietveld refinements and pair distribution function analysis. CuCrS2 exhibits a very complex phase transition in the early stage of Na uptake to form Na0.70 Cu0.15 CrS2 followed by full conversion to Cu, Cr and Na2 S. This reaction is highly reversible leading to a capacity of 424 mAh g −1, even after the 200 th cycle.